PENGARUH PEMBERIAN JENIS FESES TERNAK BERBEDA TERHADAP PRODUKSI DAN NILAI GIZI RUMPUT MOMBACA - Huljannah, Mifta; Amrullah, Amrullah; Yani, Ahmad; Sudirman, Sudirman; Hamdani, Asrul; Wahyu Satria, Edi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mombaca grass is a type of livestock feed plant with good nutritional composition and is widely used by livestock farmers in Indonesia. This study aims to determine the effect of providing different types of livestock feces on the production and nutritional value of mombaca grass. The study was conducted from January to March 2026 using a Randomized Block Design (RBD) with four treatments and four groups. Data analysis was performed through analysis of production and nutritional value using a Randomized Block Design (RBD). The results showed that all research variables, such as production and nutritional value of mombaca grass, had the highest average values for fresh weight, ranging from 0.854-1.258 kg/m2, dry weight 0.561-0.863 kg/m2, dry matter 0.477-0.747 kg/m2, ash 0.049-0.075 kg/m2, crude fat 0.002-0.006, crude fiber 0.152-0.263 kg/m2, and crude protein 0.026-0.038 kg/m2.